Unravelling the genetic and molecular mechanisms of the left-right patterning genes Pkd1l1 and Pkd2 - Dyer, LM (2022)
Pkd1 and Pkd2 encode the polycystin proteins which underlie human ADPKD, a major cause of end stage renal failure. Recently, by analysing the Pkd2lrm4 mouse, a previous member of the lab provided evidence that loss of ciliary PKD2 underlies kidney cyst formation. Furthermore, the Pkd2lrm4 mouse highlights a requirement for PKD2 in nodal cilia for correct L-R patterning. However, we are yet to fully understand its cilia-specific role and the mechanisms controlling its ciliary trafficking and entry. PKD1L1 (a PKD1 Paralog) functions with PKD2 in the embryonic node to allow correct L-R patterning and its expression and localisation during this process remain to be fully characterized.